Clinical application of color Doppler ultrasound for assessing hemodynamic changes in the children with moyamoya disease undergoing combined revascularization surgery - Zhou, Chenyun; Ji, Hang; Fan, Hongxia; Li, Yue; Han, Lina; Xiao, Anqi; Zhu, Xiaoxia; Sun, Haogeng; Tan, Zhizhi; He, Ying; Liu, Yi (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the advantages of color Doppler ultrasound (CDUS) in detecting hemodynamic alterations in children with moyamoya disease (MMD) following combined revascularization surgery.MethodsThe common carotid artery (CCA), internal carotid artery (ICA), external carotid artery (ECA), and superficial temporal artery (STA) were measured by CDUS. Hemodynamic parameters including arterial diameter, peak systolic velocity (PSV), resistance index (RI), and blood flow volume (FV) were collected at three time points: pre-operation (T1), one week after operation (T2), and three months after operation (T3). Twelve children without intracranial arterial disease were recruited as the control group. Matsushima classification-based on digital subtraction angiography (DSA) was applied at T2.ResultsAmong the 12 children with MMD, 11 patients with bilateral arterial stenosis and 1 patient with unilateral being affected. Compared to the 24 control hemispheres, the diameter of the ICA was significantly smaller in the 23 MMD hemispheres (p < 0.001) with an increased PSV of CCA and ECA, and a decrease FV of carotid arteries (p < 0.05). In MMD group, CDUS revealed increased diameter and FV, decreased RI of STA at the operative side at T2. The PSV and FV of ECA at the operative side increased from T1 to T3 (p < 0.05). Six cases were allocated to satisfactory compensation group (S Group, Matsushima classification grade A and B) and six cases to dissatisfactory compensation group (DS Group, Matsushima classification grade C). The increase in FV of STA on the operative side was higher in S Group at T2 than DS Group (Spearman rho = −0.693, p = 0.039).ConclusionAs a noninvasive imaging modality, carotid and superficial temporal arteries ultrasound may serve as a valuable adjunct to invasive imaging techniques for children with MMD.